Expanding protected areas to encompass the conservation of the endangered common dolphin (Delphinus delphis) in the Alboran Sea. (June 2021) - Giménez, Joan; Cañadas, Ana; de Stephanis, Renaud; Ramírez, Francisco
Abstract: The Natura 2000 network is the centerpiece of the European Union conservation strategy to safeguard priority species and habitats. The question of whether other co-occurring species of conservation concern may also benefit from this network, however, remains largely unknown. Here, we used a systematic approach (MARXAN) for i) evaluating if the current Natura 2000 network in the Alboran Sea (western Mediterranean Sea), initially proposed to protect the common bottlenose dolphin ( Tursiops truncatus ) and priority habitats, is also spatially protecting the endangered common dolphin ( Delphinus delphis ), and ii) identifying additional marine areas that should be protected to reach adequate conservation targets for the common dolphin. While the current Natura 2000 network encompass ca. 22% of predicted abundances for common dolphins, this percentage might be enhanced by protecting coastal areas nearby the Strait of Gibraltar. However, dolphins and fisheries largely overlap spatially nearby the coastline, and only segregate in offshore areas that represent the marginal distribution of the species. Thus, conservation decision-makers must achieve a trade-off between cetacean conservation and fisheries by combining an area-based approach ( i.e., new protected areas close to the Strait of Gibraltar) together with a basin-wide threat-based approach (e.g., regulation of fisheries). Highlights: Natura 2000 network encompass ca. 22% of predicted abundances for common dolphins. Protection might be enhanced by protecting coastal areas nearby the Strait of Gibraltar. Dolphins and fisheries largely overlap spatially nearby the coastline. Decision-makers must achieve a trade-off between cetacean conservation and fisheries.